Parks and recreation. Season seven - Holland, Dean; Magill, Tom; Poehler, Amy, 1971-; Ansari, Aziz, 1983-; Offerman, Nick, 1970- (Universal City, CA : Universal Studios Home Entertainment, 2015)
Follows a bumbling but earnest city employee as she attempts to rise through a small-town parks department.
2017 -- Ron & Jammy -- William Henry Harrison -- Leslie and Ron -- Gryzzlbox -- Save JJ's -- Donna and Joe -- Ms. Ludgate-Dwyer goes to Washington -- Pie-Mary -- The Johnny Karate super awesome musical explosion show -- Two funerals -- One last ride : part 1 -- One last ride : part 2.
Dolby digital 5.1, anamorphic wide screen 1.78:1.
Features: deleted scenes; Behind the scenes of the farewell season; gag reel; The story of Mouse Rat; commercials; The wisdom of Mayor Gunderson.
Amy Poehler, Aziz Ansari, Nick Offerman, Aubrey Plaza, Chris Pratt, Adam Scott.
Originally broadcast on television in 2015.
TV rating: Not rated.
In English with optional Spanish subtitles.
Keywords: Municipal officials and employees -- Drama; Man-woman relationships -- Drama; Parks -- Drama; Television series; Fiction television programs; Video recordings for the hearing impaired; Comedy television programs; Sitcoms; Mockumentary television programs